UPAYA INDONESIA DALAM MENGEMBANGKAN SUSTAINABLE TOURISM BERSKALA INTERNASIONAL DI NATUNA PROVINSI KEPULAUAN RIAU (KEPRI) - Anjeli, Avifa; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Currently there is a shift in tourism activities that are influenced by the environment that is more economically, socially and environmentally responsible for the local community at the destination. The occurrence of this shift directs the focus of tourism at this time not only oriented towards the level of visit alone, but can create a balance in the economic, social-cultural and environmental fields. This makes the development of tourism in Natuna into sustainable tourism (sustainable tourism), so that it can be enjoyed until the future. Achieving the goals and mission of tourism development that is good, sustainable (sustainable tourism) and environmentally sound can only be carried out when the achievement process can be done through good tourism governance, so various strategies are carried out by involving various stakeholders, bearing in mind Natuna has extraordinary natural potential of beauty and very strategic location.The research method used in this research is descriptive-qualitative which uses secondary data such as books, journals, reports, interview and the others sources. The theory used in this research is the public policy with the level of analysis is the nation state, the perspective of globalizm and supported by the concept of sustainable tourism.The research shows Indonesia's efforts in developing international-scale sustainable tourism in Natuna Riau Islands Province (KEPRI) are through the Sustainable Destination Program Development Strategy, a Strategy for the Creation of a Synergy and Environment-Friendly (Nature and Culture) Tourism Industry, Penetration Market Strategies for Environmentally Friendly Destinations, and Strategies for Building Support Institutions, through the SWOT approachKeywords : Development, Sustainable Tourism, Natuna, Strategy, Swot Analysis.